Biology and habits of Thrips palmi (Thysanoptera: Thripidae) as a pest of dry beans and snap beans - BUENO, JUAN MIGUEL; CARDONA, CÉSAR (Revista Colombiana de Entomología, 2001)
Thrips palmi Karny is a new bean pest that also affects many other important crops in Latin America. lt has also reached high economic importance in Colombia during the last two years as a pest of solanaceous crops (potato, red pepper. eggplant), cucurbits (pumpkin, watermelon, cucumber, cantaloupe) and legumes (soybean, dry beans, snap beans). The larvae of this polyphagous insect prefer to feed on the underside of the leaf, causing deformations, bronze coloring, and defoliation. Adults are preferably found on the upper face of the leaf, on tender buds, and on flowers. The biology of this insect as a pest of beans was studied in laboratory conditions at 25 ± 2ºC, 65 ± 5% H.R. and 12-hour photoperiod. lt was found that the duration in days of the immature stages (± S.D) was: egg, 4 ± 1.1; first instar, 2.2 ± 1.0; second instar, 1.3 ± 1.1; prepupa, 2.6 ± 1.0; pupa, 2.7 ± 2.3. The total duration of the egg to adult emergence was estimated at 12.6 ± 3. 7 days. The longevities of males and females were 16.5 ± 5.5 y 17.0 ± 7.1 days, respectively. After a preoviposition period of 4.5 ± 1. 7 days, mated females laid an average of 30 ± 22 eggs, in an oviposition period of 13 ± 7.7 days. The estimated viability of eggs was 92%.